(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents ideas about the role and significance of public associations as a certain part of a non-profit organization. Public associations are one of the important links of non-governmental non-profit organizations in society. Having thoroughly mastered it, you can obtain information about public associations, their organizational and legal foundations, their role in the political system of society, their significance, forms of public associations and the order of their membership.